Bridging the Gap: Environmental Education as a Catalyst for Human-Environmental Harmony - Harahap, Dakkal; Uthman, Yusuf Olawale Owa-Onire (CV. Bimbingan Belajar Assyfa, 2024)
Human activities are increasingly disrupting the balance between economic development and environmental sustainability, highlighting the urgent need for effective environmental education. This study investigates how environmental education functions as a catalyst for fostering harmonious relationships between humans and the natural surroundings. We address the urgent problem of environmental degradation driven by the prioritization of business interests over ecological well-being and explore how informed human resources can mitigate these impacts. This research uses a systematic literature review (SLR) methodology, which utilizes the PRISMA technique to analyze various literature sources, including books, journal articles, and reviews. Data collection focuses on publications from the Scopus database in the period April 2019 to May 2024, using keywords such as